HIV retesting prevalence among clients accessing anti-retroviral therapy and HIV testing services in Ghana - Raphael Adu-Gyamfi; Stephen Ayisi Addo; Nyonuku Akosua Baddoo; Ernest Kenu; Anthony Ashinyo; Kwadwo Koduah Owusu; Menard Laurent Chihana; Alice Sallar Adams; Odikro Magdalene; Delia Bandoh; Marijanatu Abdulai; Kenneth Danso; et al. (PLoS ONE, 2025)
Introduction Ghana is working towards achieving the 95-95-95 targets for its HIV response. One challenge has been low linkage to care rates, possibly due to high rates of retesting among people living with HIV who are already aware of their status. This leads to an overestimation of the first 95 and a subsequent underestimation of the second 95. This study aimed to measure the prevalence of HIV retesting among PLHIV in Ghana who are already aware of their status and to explore their reasons for retesting. Methods This was a facility-based cross-sectional study conducted in the three ecological zones of Ghana. A total of 11,145 individuals from 30 ART centres and 90 HTS centres participated. The sample size for each zone was determined proportionally based on the number of people enrolled in ART. A profiling tool was used to assess testing behaviours among clients visiting HTS sites linked to ART clinics. Focus group discussions were also conducted with clients and health workers to gather their perceptions of reasons for retesting. Results Participants were predominantly female (74.3%; 8,285/11,145), with a median age (interquartile range) of 43.0 (35–52). The prevalence of retesting among ART clients was 32.9% [95% CI: 0.32–0.34] (3,670/11,145). Among those who retested, the majority did so twice (2,041; 55.6%). Of the clients who tested positive for HIV during the study period, 53.1% (43/835; 95% CI: 0.49–0.57) had a previous HIV diagnosis. Adjusting for retesting, the positivity rate at HTS sites decreased from 8.4% to 4.1%. Key reasons for retesting included the desire to confirm diagnosis, denial and doubt regarding test results, retesting required due to documentation issues, and religious beliefs. Conclusion The prevalence of retesting over the past six years was found to be high, resulting in an overestimation of HIV positivity rates and affecting linkage to care. Implementing interventions to accurately account for retesting instances may improve data accuracy and the country’s linkage to care rate, bringing Ghana closer to achieving the 95-95-95 targets.